2019
DOI: 10.1016/j.apsb.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrellin A-based photodynamic action induces apoptosis in A549 cells through ROS-mediated mitochondrial signaling pathway

Abstract: Over recent decades, many studies have reported that hypocrellin A (HA) can eliminate cancer cells with proper irradiation in several cancer cell lines. However, the precise molecular mechanism underlying its anticancer effect has not been fully defined. HA-mediated cytotoxicity and apoptosis in human lung adenocarcinoma A549 cells were evaluated after photodynamic therapy (PDT). A temporal quantitative proteomics approach by isobaric tag for relative and absolute quantitation (iTRAQ) 2D liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…Loss of MMP causes the release of proteins located in the intermembrane space of the mitochondria [28], including several important apoptosis-inducing factors, such as cytochrome c, which activates caspase 9, leading in turn to caspase 3 activation [29,30]. In addition, loss of MMP can disrupt the balance between pro-apoptotic Bax and anti-apoptotic Bcl-2 levels in mitochondria [31,32]. Zhou et al showed that calcitonin gene-related peptide (CGRP) together with substance P reduce melanogenesis, while CGRP exerts a dose-dependent apoptotic effect in B16F10 melanoma cells through increased expression of caspases 3 and 9 and reduced Bax/Bcl-2 ratio [33].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MMP causes the release of proteins located in the intermembrane space of the mitochondria [28], including several important apoptosis-inducing factors, such as cytochrome c, which activates caspase 9, leading in turn to caspase 3 activation [29,30]. In addition, loss of MMP can disrupt the balance between pro-apoptotic Bax and anti-apoptotic Bcl-2 levels in mitochondria [31,32]. Zhou et al showed that calcitonin gene-related peptide (CGRP) together with substance P reduce melanogenesis, while CGRP exerts a dose-dependent apoptotic effect in B16F10 melanoma cells through increased expression of caspases 3 and 9 and reduced Bax/Bcl-2 ratio [33].…”
Section: Discussionmentioning
confidence: 99%
“…Staining. DCFH-DA staining was performed to evaluate ROS generation in H9c2 cells via referring to previous studies [39]. In brief, cells were incubated with DMEM medium containing 10 μmol/L DCFH-DA (Beyotime Biotechnology, China) for half an hour at 37°C, and then the images were captured by an Olympus IX53 fluorescence microscope in a blinded manner.…”
Section: ′ 7 ′ -Dichlorodihydrofluorescein Diacetate (Dcfh-da)mentioning
confidence: 99%
“…The lung homogenates or cell lysates were incubated with DCFH-DA (50 μ mol/L) at 37°C for 30 min in the dark [ 29 , 30 ]. DCF fluorescence intensities were then measured using a Bio-Tek microplate reader at the excitation and emission wavelengths of 485 nm and 535 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%